Influence of irradiation on indicatory surface of anelastic-elastic body of AgZn alloy - Yurii Onanko; Lyudmyla Kuzmych; Anatoliy Onanko; Oksana Dmytrenko; Tetiana Pinchuk-Rugal; Serhii Usatyi; Peter Il’in; Stepan Kuzmych (Materials Research Express)
The temperature dependence of internal friction Q ^−1 and elastic modulus Е (‘indicatory surface of anelastic-elastic body’) of Ag _0.8 Zn _0.2 alloy was studied. After electron irradiation, sharp exponential growth of internal friction background Q ^−1 _b was observed at temperatures T > 610 K. The effect of radiation exposure on the temperature dependence of internal friction Q ^−1 and elastic modulus Е of Ag _0.8 Zn _0.2 alloy, which is ordered, was studied. The temperature intervals of formation and rearrangement of the short-range order were determined. The influence of electron irradiation and thermomechanical treatment on the short-range ordering processes of AgZn solid solutions was studied. After electron irradiation, the temperature dependence of internal friction Q ^−1 and elastic modulus Е (‘indicatory surface of anelastic-elastic body’) of Ag _0.8 Zn _0.2 alloy revealed internal friction maximum Q ^−1 _М1 at temperature T _М1 ≈ 560 K.